Kajian Industri Arang Dari Kayu Akasia (Acacia mangium) Di Kecamatan Bumi Nabung Kabupaten Lampung Tengah - Kinanti, Sekar; Haryanto, Agus; Kuncoro, Sapto; Suharyatun, Siti (abe.fp.unila.ac.id, 2022)
One way to increase the energy and economic value of wood waste is to convert it into charcoal through the pyrolysis process. The purpose of this study was to determine the performance of the acacia wood charcoal industry and the characteristics of acacia wood charcoal. Data collection was carried out by observing the production process of acacia wood charcoal in Bumi Nabung District, Central Lampung Regency. Parameters included charcoal yield, processing capacity, charcoal characteristics (bulk density, moisture content, ash content, water absorption, and calorific value), and economic analysis of small-scale charcoal industry. The results showed that the production system still uses traditional methods, starting from the preparation of raw materials, preparation of raw materials, installation of boxes, adding soil to the boxes, burning, cooling and harvesting. Based on cooling method, charcoal production was grouped into two, namely natural and water spraying cooling. Sprayed charcoal has the characteristics of water content 5.1%, ash content 2.99%, bulk density 0.256 g/cm3 and calorific value 30.42 MJ/kg. While the characteristics of natural cooled charcoal were 2.52% moisture content, 1.78% ash content, 0.123 g/cm3 bulk density and calorific value 32.93 MJ/kg. The monthly profit obtained wass IDR656.918,64 for sprayed charcoal and IDR167.227,46 for natural charcoal. Keywords: Acacia, Charcoal, Cooling, Pyrolysis, Yield.